Multimodal Biosensing on Paper-Based Platform Fabricated by Plasmonic Calligraphy Using Gold Nanobypiramids Ink - Campu, Andreea; Susu, Laurentiu; Orzan, Filip; Maniu, Dana; Craciun, Ana Maria; Vulpoi, Adriana; Roiban, Lucian; Focsan, Monica; Astilean, Simion (Frontiers in Chemistry, 2019)
In this work, we design new plasmonic paper-based nanoplatforms with interesting capabilities in terms of sensitivity, efficiency and reproducibility for promoting multimodal biodetection via Localized Surface Plasmon Resonance (LSPR), Surface Enhanced Raman Spectroscopy (SERS) and Metal Enhanced Fluorescence (MEF). To succeed, we exploit the unique optical properties of gold nanobipyramids (AuBPs) deposited onto the cellulose fibers via plasmonic calligraphy using a commercial pen. The first step of the biosensing protocol was to precisely graft the previously chemically-formed p-aminothiophenol@Biotin system, as active recognition element for target streptavidin detection, onto the plasmonic nanoplatform. The specific capture of the target protein was successfully demonstrated using three complementary sensing techniques. As a result, while the LSPR based sensing capabilities of the nanoplatform were proved by successive 13 to 18 nm red shifts of the longitudinal LSPR associated with the change of the surface RI after each step. By employing the ultrasensitive SERS technique, we were able to indirectly confirm the molecular identification of the biotin-streptavidin interaction due to the protein fingerprint bands assigned to amide I, amide III and Trp vibrations. Additionally, the formed biotin-streptavidin complex acted as a spacer to ensure an optimal distance between the AuBP surface and the Alexa 680 fluorophore for achieving a 2-fold fluorescence emission enhancement of streptavidin@Alexa 680 on the biotinylated nanoplatform compared to the same complex on bare paper (near the plasmonic lines), implementing thus a novel MEF sensing nanoplatform. Finally, by integrating multiple LSPR, SERS and MEF nanosensors with multiplex capability into a single flexible and portable plasmonic nanoplatform, we could overcome important limits in the field of portable point-of-care diagnostics.